Problematika Penerapan Aspek Psikomotorik Mata Pelajaran PAI Dalam Aktivitas Sehari-Hari Siswa SMK PGRI 2 Ponorogo - Artiani Tian (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
This research aims to analyze the problems of implementing the psychomotor aspects of Islamic Religious Education (PAI) learning in the daily activities of students at SMK PGRI 2 Ponorogo and identify the solutions to be applied. The approach in this research is qualitative with a case study type. The selection of subjects is based on the consideration that students are less able to apply psychomotor aspects in everyday life. The methods used to collect data are interviews and observation. The research results show that the main challenges in implementing psychomotor aspects in students' daily activities include: (1) variations in students' abilities. (2) students' lack of awareness of the importance of the practice of worship. (3) Limited facilities and infrastructure. (4) Lack of support from parents. To overcome this problem, schools implement various strategies, including flexible memorization methods, Islamic boarding school programs to familiarize themselves with worship practices, as well as the use of problem-based and cooperative learning strategies. This research emphasizes the importance of synergy between schools, teachers and families in supporting the development of psychomotor aspects so that students are able to apply them consistently in everyday life.